2022
DOI: 10.3390/brainsci12111520
|View full text |Cite
|
Sign up to set email alerts
|

Deficit Symptomatology of Schizophrenia Is Associated with Attenuated Taste Identification: Findings from a Cross-Sectional Study

Abstract: Schizophrenia is the subject of many studies. There have been reports of taste disturbances in mental disorders. We found a possible relationship between deficit symptoms of schizophrenia and the dysgeusia of monosodium glutamate (MSG). Dysgeusia is a disorder that distorts the sense of taste. People describe all foods as tasting sweet, sour, bitter, or metallic. We aimed to verify whether the level of MSG taste perception may be related to the severity of deficit symptoms. MSG detection threshold was assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies have focused on pathologic, radiologic, and biologic data, and many predicting systems have been developed [ 7 , 8 , 9 ]. The treatment design should be delicately discussed by a multidisciplinary team to incorporate ablation, trans-arterial chemoembolization (TACE), and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have focused on pathologic, radiologic, and biologic data, and many predicting systems have been developed [ 7 , 8 , 9 ]. The treatment design should be delicately discussed by a multidisciplinary team to incorporate ablation, trans-arterial chemoembolization (TACE), and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found a significant negative correlation between mean intensity of taste and the number of deficit symptoms. The study suggest that the symptoms of taste disturbances reported by the patient should be monitored by clinicians and in order to differentiate between the actual deficits in the domain of taste perception and taste hallucinations as a symptom of psychosis [ 10 ].…”
mentioning
confidence: 99%